Influencia de la acidez y temperatura del proceso de hilado del queso tipo “de hoja” sobre las propiedades físico química, sensoriales y microbiológicas - Marcillo Salazar, Yessenia Natali (2016)
It assessed the physical and chemical characteristics and sensorial characteristics of microbiological sheet cheese under different conditions of yarn. It was used a completely randomized design with a factorial arrangement of 2x2, acidity levels of serum (1.10 % and 0.87 %) and temperature levels of the yarn (68°C and 80°C). In the physical-chemical: Total solids; acidity; pH; fat and protein, sensory characteristics of texture, flavor and odour: stretching and penetration, determined the cost of the treatments. The levels of yarn had effect (p<0.05) on the physical and chemical characteristics of the cheese with difference (p>0.05) in the factors of total solids, acidity, fat and protein, while in the pH there is no difference, so that by increasing the acidity loses the characteristics that gets the cheese at the time of the yarn. In the analysis of the sensory characteristics of texture of the cheese the attribution of viscosity and elasticity decreased (p<0.05) with the highest level of the acidity (0.87 %), while the characteristics of hardness, masticabilidad and gomosidad was accentuated in this level, in that factor is not presented differences (p<0.05) in the cohesion and fracturabilidad. The increase in the temperature of the yarn increased sensory perception of cohesion and elasticity in the viscosity characteristics and masticabilidad decreased, hardness, and fracturabilidad gomosidad did not show differences (p>0.05). In the sensory analysis of scent and flavor of the cheese the increase of the acidity and temperature of yarn reduces (p<0.005) the sensory characteristics of smell of milk, creaminess, fatness, color ivory, pastosidad and bitter flavor of the cheese, increases (p<0.005) the perception of the level of salt. The higher (p<0.05) performance obtained the 1.10 % of acidity and 80°C of temperature of yarn respectively, in the test of stretching. The most efficient treatment was T4 due to its higher performance.